Electronic and transport properties of graphene nanoribbon barbell‐shaped heterojunctions. Issue 11 (5th August 2013) - Price, Miles D. S.; Cruz‐Silva, Eduardo; Luiza Mariano Torres Costa, Ana; Morais de Vasconcelos, Fabrìcio; Girão, Eduardo Costa; Zhang, S.B.; Meunier, Vincent; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; Richter, Klaus; Weber, Heiko
Abstract We study the electronic transport properties of graphene nanoribbon barbell systems using a combination of density functional theory and Landauer–Büttiker electronic transport theory to establish the relationship between the conduction gaps of barbell‐shaped graphitic heterojunctions and those of their constituting elements. The barbells considered in this study are built from graphene nanoribbons (GNRs) with either a zigzag or armchair mono‐hydrogen terminated edge structure. The mechanism of bandgap variations is rationalized on the existence of specific boundary conditions imposed on the spin distribution at the interface, as well as on the property of the junction channel. It is established that the nature of the spin polarized conductance pattern depends significantly on the type of graphene nanoribbon edge and the coupling between the two graphene nanoribbon sublattices. The findings highlight the difficulty of exploiting the intrinsic properties of pristine zigzag GNRs when they are placed between electrodes, even when the contact is seamless and defect‐free, since the intrinsic mismatch between the zigzag sectors induce a long‐range spin defect state that affects that dictates the details of the conduction gap of the assembly.